ANALISIS KINERJA KEUANGAN PEMERINTAH KABUPATEN KARANGANYAR TAHUN ANGGARAN 2013 – 2015 - Djoko Kristianto, Susilowati, Suharno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this study is to analyze the financial performance optimization in Karanganyar regency government by using financial ratio indicators of the budget for Fiscal Year 2013-2015. The research method using the case study method in Karanganyar district administration, the type of data used quantitative and qualitative data, the data source used secondary data. Data collection methods used documentation. The method used descriptive quantitative method to measure financial performance with financial ratios. In conclusion that: 1) The results of the analysis of the ratio of the degree of fiscal decentralization Karanganyar years 2013 to 2015 show in 2013. The ratio of Degree of Fiscal Decentralization on Local Government Karanganyar of 9,81%. In 2014 decreased to 9,76%, the next year increased to 11,21% occurred in the category less. 2) The results of the analysis of the dependency ratio Karanganyar years 2013-2015 show financial dependence is relatively low. 3) The results of the analysis of the ratio of local financial independence in 2013 to 2015 showed Karanganyar Karanganyar financial capability is still relatively very low and relationship patterns including patterns instructive relationship where the role of central government is more dominant than the independence of local government (areas that are not capable of implementing regional autonomy), 4) The results of the analysis of effectiveness ratio of PAD Karanganyar years 2013 to 2015 show that the effectiveness of the Local Government Finance Karanganyar in 2013 and 2014 is quite effective, and 2015 was very effective. 5) The results of the analysis of regional spending efficiency ratio Efficiency Ratio Regional Shopping Karanganyar years 2013-2015 as very efficient for intervals of less than 10% efficiency.Keywords: financial ratios, financial performance of local government